ANALISIS PERILAKU BIAYA PEMELIHARAAN MESIN PADA PT MANDIRI MUKTI KEPAHIANG - Adetanza Qomaria (Politeknik Raflesia Press, 2020)
This research to know behavior of machine maintenance cost at PT. SaranaMandiriMuktiKepahiang Regency in the Year 2017 s / d tahun2019 so it can know how the maintenance costs of the machine can change in line with changes in the volume of activities in the machine hours. So it can make it easier for companies to analyze the potential costs that will arise in the future and can assess the nominal fairness of costs that occur. The analysis used in this research is descriptive anaslisis method, that is by collecting, presenting, and analyzing data from PT. Sarana Mandiri Mukti based on facts. The author uses cost behavior analysis with the highest and low point method, the stanby cost method, and the smallest quadrad method (Least Square Method) to separate variable costs and fixed costs. Result of research can be concluded that machine maintenance cost happened at PT. Mukti Mandiri's facilities each year change according to changes in the volume of activities but the nature of the changes are not proportional to or disproportionate to changes in the volume of activities. The relationship between machine clock and machine maintenance cost can be expressed in the cost function of a linear function Y = a + b X its function equation (Y = 1.227 + 841 X)